Health Care Utilization and Costs Associated with Adherence to Clinical Practice Guidelines for Early Magnetic Resonance Imaging among Workers with Acute Occupational Low Back Pain - Graves, Janessa M (Blackwell Publishing Ltd, 2014)
OBJECTIVE: To estimate health care utilization and costs associated with adherence to clinical practice guidelines for the use of early magnetic resonance imaging (MRI; within the first 6 weeks of injury) for acute occupational low back pain (LBP). DATA SOURCES: Washington State Disability Risk Identification Study Cohort (D-RISC), consisting of administrative claims and patient interview data from workers’ compensation claimants (2002–2004). STUDY DESIGN: In this prospective, population-based cohort study, we compared health care utilization and costs among workers whose imaging was adherent to guidelines (no early MRI) to workers whose imaging was not adherent to guidelines (early MRI in the absence of red flags). DATA COLLECTION/EXTRACTION METHODS: We identified workers (age >18) with work-related LBP using administrative claims. We obtained demographic, injury, health, and employment information through telephone interviews to adjust for baseline differences between groups. We ascertained health care utilization and costs from administrative claims for 1 year following injury. PRINCIPAL FINDINGS: Of 1,770 workers, 336 (19.0 percent) were classified as nonadherent to guidelines. Outpatient and physical/occupational therapy utilization was 52–54 percent higher for workers whose imaging was not adherent to guidelines compared to workers with guideline-adherent imaging; utilization of chiropractic care was significantly lower (18 percent). CONCLUSIONS: Nonadherence to guidelines for early MRI was associated with increased likelihood of lumbosacral injections or surgery and higher costs for out-patient, inpatient, and nonmedical services, and disability compensation.